2019
DOI: 10.9734/arrb/2019/v32i230076
|View full text |Cite
|
Sign up to set email alerts
|

Renal Protective Effect of Ginkgo biloba and L-carnitine Extracts against Pentylenetetrazol Induced Toxicity, Oxidative Stress, Injury and Proliferation Alternation in Epileptic Rats

Abstract: Objectives: Ginkgo biloba leaf extract (GBLE) and L-carnitine extract are a commercial product used as a nutraceutic herbal widely. They have antioxidant and reactive oxygen species (ROS) scavenger. This study hypothesized that GB and L-carnitine may have protective effects against pentylenetetrazol (PTZ) induced oxidative damage in kidney in male albino rats. Materials and Methods: A total of 80 male albino rats were equally divided into eight groups (G1, control; G2, GBLE; G3, L-carnitine; G4, Pentylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…In contrast; a significant decrease in serum potassium and calcium ions were detected in Amitriptyline group when compared with control group. Our results were consistent with Tousson et al [9,34] who reported that; amitriptyline induced an increase in sodium ions levels and decrease in potassium ions level.…”
Section: Fig 3 Changes In Serum Sodium Ions (Mmol/i) Potassium Ionsupporting
confidence: 94%
“…In contrast; a significant decrease in serum potassium and calcium ions were detected in Amitriptyline group when compared with control group. Our results were consistent with Tousson et al [9,34] who reported that; amitriptyline induced an increase in sodium ions levels and decrease in potassium ions level.…”
Section: Fig 3 Changes In Serum Sodium Ions (Mmol/i) Potassium Ionsupporting
confidence: 94%
“…Similar to our results, Tousson et al . reported improved renal function parameters accompanied by significant antioxidant effects of L-carnitine against pentylenetetrazol-induced renal injury as was apparent by reduced total antioxidant capacity and MDA concentrations and catalase and superoxide dismutase activities ( 12 ). Kunak et al .…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine is endogenously synthesized in the liver, kidneys, and brain ( 11 ). L-carnitine improves mitochondrial functionality thus plays an essential role in energy production via fatty acids transportation into mitochondria ( 12 ). L-carnitine metabolism occurs mainly in the kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, kidney DNA fragmentation and MDA levels increased with PTZ. They also suggested that total antioxidant capacity decreased (Tousson et al 2019). In their study conducted by different research groups, they reported that PTZ administration increased lipid peroxidation in the kidney, but there was no change in endogenous antioxidant levels (Kapucu et al 2021;Uma Devi et al 2006).…”
Section: Discussionmentioning
confidence: 97%